The application of management accounting principles in the Emfuleni local municipality minibus taxi industry - Mukhodeni, Mbobo Muthige (Vaal University of Technology, 2022)
The minibus taxi industry in South Africa is one of the biggest, fastest growing, and riskiest industries in the world. The minibus taxi industry contributes to the economy by creating over 600,000 jobs, providing fast and cheap transport and fighting poverty and unemployment. However, the recent COVID 19 pandemia restrictions has caused a sudden and movement of economic growth and competition has forced the minibus taxi industry to be competitive in all aspects. This has resulted in intense competition for minibus taxi owners. Minibus taxi owners are constantly in rivalry amongst themselves and with other public road transport providers. In early 1988, the minibus taxi industry started seeing an influx in the number of new minibus taxis and minibus owners. This influx created problems of competition within the industry and among minibus taxi owners. Due to the importance of this industry, this research study investigated whether minibus taxi owners in the Emfuleni Local Municipality apply selected management accounting principles in the management of their minibus taxi businesses. Selected management accounting principles in this study refers to cost volume profit analysis, cost structure, and budgeting. This research study followed a quantitative research design and a questionnaire was used to collect primary data from a census of 500 minibus taxi owners from the following five associations: Get Ahead Taxi Association (GATA), Vaal National Taxi Association (VNTA), Vanderbijlpark Taxi Association (VTA), Sharpeville to Vereeniging and Vanderbijlpark Taxi Association (SVVTA) and Civic Centre Taxi Association (CCTA) operating in the Emfuleni Local Municipality. Using descriptive statistical analysis to present the findings, the study used Statistical Package for Social Sciences Version 27. Findings obtained using an online questionnaire and printed questionnaire distributed revealed a lack of management accounting principles application among these minibus taxi owners. Furthermore, the minibus taxi owners do not apply cost volume profit analysis and most do not use budgets. However, it was found that some minibus taxi owners apply very basic cash budgeting through a pen-on-paper approach. It was also found that minibus taxi owners understand the application of cost structures. This research study recommends that minibus taxi owners should be offered training by skills sectors to apply the selected management accounting principles. The limitations of this research study included that the census was geogracial restrictions, level of education, and corona virus restrictions. Despite these limitations, the research study was able to fulfil its main objective by determining that majority of minibus taxi owners do not apply the selected management accounting principles.
M. Tech. (Department of Accountancy, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Management accounting; Selected management accounting principles; Cost volume profit analysis; Cost structure; Budgeting; Minibus taxi industry; Minibus taxi owner; Emfuleni Local Municipality; Social responsibility of business.; Managerial accounting.; Dissertations, Academic -- South Africa.; Cost accounting.; Accounting.; Budget in business.